Experimental Studies and the Search for New Innovative Approaches to Treat Dry Eye Disease - Liemienieva, Anastasiia; Shargorodska, Iryna; Rykov, Sergiy; Petrovsky, Mykola (Journal of Education, Health and Sport, 2021)
Introduction and purpose. The main manifestation of eyelids, tear ducts, and orbits disorders is a dry eye disease considered as a serious disease that affects the quality of life. Nowadays, one in ten people worldwide faces this disease. Increased workload, development of multimedia technologies, hypodynamia, and environmental degradation are the main modern causes of the disease. Material and methods. In this work, we used an experimental model of dry eye in rats with the development of inflammation of the anterior surface of the eye. Alkali burns were used to develop inflammation. A fluorescein test performed immediately after alkaline erosion and on days 1, 5, and 10 after burns revealed a gradual increase in corneal epithelialization and vascularization. Results. One day after induction of inflammation, there was a dramatic and statistically significant increase in tear production in experimental rats. By the seventh day, tear production declined to the control level with a subsequent tendency to decrease tear production. Conclusions. In the group of rats with inflammation of the anterior surface of the eye that received polarized red-light therapy, there was no significant decrease in tear production on day 7, which may be indicative of a possible anti-inflammatory effect of light therapy under these conditions.